The SXS collaboration catalog of binary black hole simulations. (11th September 2019) - Boyle, Michael; Hemberger, Daniel; Iozzo, Dante A B; Lovelace, Geoffrey; Ossokine, Serguei; Pfeiffer, Harald P; Scheel, Mark A; Stein, Leo C; Woodford, Charles J; Zimmerman, Aaron B; Afshari, Nousha; Barkett, Kevin; et al.
Abstract: Accurate models of gravitational waves from merging black holes are necessary for detectors to observe as many events as possible while extracting the maximum science. Near the time of merger, the gravitational waves from merging black holes can be computed only using numerical relativity. In this paper, we present a major update of the Simulating eXtreme Spacetimes (SXS) Collaboration catalog of numerical simulations for merging black holes. The catalog contains 2018 distinct configurations (a factor of 11 increase compared to the 2013 SXS catalog), including 1426 spin-precessing configurations, with mass ratios between 1 and 10, and spin magnitudes up to 0.998. The median length of a waveform in the catalog is 39 cycles of the dominant gravitational-wave mode, with the shortest waveform containing 7.0 cycles and the longest 351.3 cycles. We discuss improvements such as correcting for moving centers of mass and extended coverage of the parameter space. We also present a thorough analysis of numerical errors, finding typical truncation errors corresponding to a waveform mismatch of ̃10 −4 . The simulations provide remnant masses and spins with uncertainties of 0.03% and 0.1% (90th percentile), about an order of magnitude better than analytical models for remnant properties. The full catalog is publicly available atwww.black-holes.org/waveforms .